2013
DOI: 10.1111/nph.12496
|View full text |Cite
|
Sign up to set email alerts
|

Effects of natural hybrid and non‐hybridEpichloëendophytes on the response ofHordelymus europaeusto drought stress

Abstract: SummaryInterspecific hybrid endophytes of the genus Epichlo€ e (Ascomycota, Clavicipitaceae) are prevalent in wild grass populations, possibly because of their larger gene variation, resulting in increased fitness benefits for host plants; however, the reasons are not yet known. We tested hypotheses regarding niche expansion mediated by hybrid endophytes, population-dependent interactions and local co-adaptation in the woodland grass Hordelymus europaeus, which naturally hosts both hybrid and non-hybrid endoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 58 publications
3
40
1
4
Order By: Relevance
“…Bromus laevipes has a narrow distribution limited to the United States west coast, yet the number of distinct Epichlo€ e species hosted by this grass, and the extensive chemotypic variation within, suggests that considerably more diversity exists within Epichlo€ e species in other hosts. Other studies have identified single host populations that harbor multiple endophyte species, but have not yet determined the chemotypic diversity among and between these species (Moon et al, 2004;Iannone et al, 2012;Leuchtmann & Oberhofer, 2013;Card et al, 2014;Oberhofer et al, 2014). Recent collections of the European woodland grass Hordelymus europaeus, spanning the latitudinal distribution transect of this host were found to associate with six distinct Epichlo€ e taxa (Oberhofer & Leuchtmann, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Bromus laevipes has a narrow distribution limited to the United States west coast, yet the number of distinct Epichlo€ e species hosted by this grass, and the extensive chemotypic variation within, suggests that considerably more diversity exists within Epichlo€ e species in other hosts. Other studies have identified single host populations that harbor multiple endophyte species, but have not yet determined the chemotypic diversity among and between these species (Moon et al, 2004;Iannone et al, 2012;Leuchtmann & Oberhofer, 2013;Card et al, 2014;Oberhofer et al, 2014). Recent collections of the European woodland grass Hordelymus europaeus, spanning the latitudinal distribution transect of this host were found to associate with six distinct Epichlo€ e taxa (Oberhofer & Leuchtmann, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The asexual species of this genus had previously been classified as Neotyphodium spp. (Leuchtmann et al 2014). Previous studies that have focused mainly on species that are endophytes of Lolium and Festuca spp., have reported that endophyte infection may increase host resistance to biotic (Meister et al 2006;H€ arri et al 2009;Saari et al 2010;Vignale et al 2013;Matsukura et al 2014;Thom et al 2014) and abiotic stresses (Malinowski et al 2005;M€ uller and Krauss 2005;Schardl et al 2007;Oberhofer et al 2014).…”
Section: Introductionmentioning
confidence: 98%
“…There are three sources of variation that may change interaction outcomes: (1) endophyte strain or species, (2) host plant genotype, and (3) the local abiotic (e.g., soil nutrients and moisture) and biotic (e.g., the presence of herbivores and natural enemies of herbivores) environments. Recent molecular studies show remarkable genetic variation in Epichloë endophytes (e.g., [4]) across host grass species but also within a given grass species (e.g., [9]). Host phenotypic differences stemming from different endophyte strains may even be greater than that from infection itself (e.g., [10]).…”
Section: Introductionmentioning
confidence: 99%